P23 Q/A METHOD -A novel way of assessing pulmonary artery stiffness in COPD using cardiac MRI. (12th November 2015) - Saikia, S; Gale, NS; Rodrigues, JCL; Wise, RG; Bucciarelli-Ducci, C; Cockcroft, JR; Shale, DJ
Abstract : Background: Pulmonary artery distensibility and pulsatility has been studied in patients with COPD using cardiac MRI (CMRI). 1 However, pulmonary artery pulse wave velocity (PA-PWV) using the 'QA'method 2 in CMRI has not been studied in this population. We hypothesised that patients with COPD have a higher PA-PWV compared to healthy individuals. Methods: This interim analysis includes 23 COPD and 12 healthy volunteers (current or ex-smokers free from respiratory disease). All participants underwent spirometry to measure FeV1, FVC and their ratio, oxygen saturations, heart rate, peripheral mean arterial pressure (MAP), 6-minute-walk-distance (6MWD) and cardiac MRI to measure PA-PWV. MRI studies were performed using a 3.0T GE Signa HDx MRI scanner (GE Healthcare). Phase-contrast cross-sectional images of the pulmonary artery using steady-state free precession sequence were obtained, approximately 2 cm above the pulmonary valve, under free-breathing conditions. Results: Patients with COPD and the healthy individuals were similar in age and gender (Table 1 ). Patients with COPD had impaired lung function, greater PA-PWV (3.37 ± 0.62 vs 1.4 ± 0.4, p = <0.001*), heart rate and mean arterial pressure than the healthy individuals. Male patients with COPD had greater PA-PWV (3.63 ± 0.45) than females (3.11 ± 0.59) p = 0.042. PA-PWV did not relate to age, lung function, resting oxyyen saturations, heart rate or peripheral MAP. Conclusion: Pulmonary artery PWV measured using CMRI 'QA' method showed that COPD patients have a stiffer pulmonary artery than healthy individuals. Further analysis will investigate the association between pulmonary artery stiffness and cardiac function. References: 1 Liu C-Y, Jiang R, Dashnaw S, et al . Pulmonary artery stiffness in chronic obstructive pulmonary disease (COPD) - the MESA COPD study. JCMR 2011;13 (Suppl 1):P73 2 Peng H-H, Chung HW, Yu HY, Tseng WY. Estimation of pulse wave velocity in main pulmonary artery with phase contrast MRI: preliminary investigation. JMRI 2006;24 :1303–1310